Синтезатор алгоритмов и программ ОКПТО–2014. Структура, область применения, дальнейшие пути совершенствования - Каневец, Георгий Евдокимович; Алтухова, Ольга Васильевна (НТУ "ХПИ", 2014)
В статье изложена общая структура системы синтеза алгоритмов и программ ОКПТО 2014 для оптимизации пластинчатых и кожухотрубных теплообменников. Также представлены некоторые пути развития этой системы с целью расширения области ее применения для специфических конструкций теплообменников и условий теплообмена.

In this paper the general structure of the synthesis for synthesizers the means of calculation and optimization of heat transfer equipment for different appointments and designs are described OKPTO 2014. Also presents some ways of development of this system in order to expand its applicability to the specific design of heat exchangers and heat transfer conditions.
Synthesizer algorithms and programs OKPTO‒2014. Structure, scope, further ways of improving
Keywords: аппарат теплообменный; оборудование; эффективность